Centro de investigación y desarrollo tecnológico para los recursos hídricos de la cuenca del Río Magdalena – Hidroindectec (2018)
The Magdalena River basin is one of the regions with the highest incidence for the country's productivity, this being one of the most important fluvial channels due to the connection between the exterior and the interior of the country. Over the years, the whole world has been going through various changes at the social, economic, political and environmental levels, evidencing a high impact at the global level, whereby the different major cities of the world impose certain regimes that indirectly generate at a global level, the challenge and the need to increase their productivity in order to improve their competitiveness, production and improve their income, both monetary and material, in order to promote in an innovative and sustainable way a society that responds and positive results to said process and changes present in the future. However, the productivity and quality of life of these territories has been declining in recent decades, due to the lack of technology in river ports, pollution in natural resources and the lack of technology and job training, which guarantee the emphasis in territorial vocations, and innovation for the economic boom of the region.